Sequential Treatment of Food Industry Wastewater by Electro-Fenton and Electrocoagulation Processes - Dindas, Gizem Bayaran; Caliskan, Yasemin; Celebi, Emin Ender; Tekbas, Mesut; Bektaş, Nihal; Yatmaz, Hüseyin Cengiz (Esg, 2018)
The food industry is one of industrial activity that use large amounts of water and as a consequence of various consumption stages in the process, the quantity and the composition of wastewater can be significantly ranged. In this study, high strength of food industry wastewater was treated by electro-Fenton (EF) and electrocoagulation (EC) process was sequentially applied to remove total organic carbon (TOC) from wastewater. During EF process, H2O2 amount was periodically added based on the calculated amount of released iron content from anode electro-dissolution. Then, EC process was further carried out to finalize the sequential treatment process. Optimum reaction time for EF process was initially investigated then the ideal current density value was determined for EC process with iron plate electrodes. This tandem sequential treatment processes resulted in 58.7 % TOC, 93.9 % total phosphate, 82.8 % TSS and 74.4 % turbidity reduction at 120 min EF (5mA/cm(2)) and 180 min EC (15mA/cm(2)) by applying optimum operation conditions. The electrode and energy consumptions were calculated as 13.43 kg/m(3) and 31.26 kWh/m(3), respectively in EF+EC processes.
Keywords: Food industry wastewater; electrocoagulation; electro-Fenton; sequential treatment